2019
DOI: 10.1002/bio.3701
|View full text |Cite
|
Sign up to set email alerts
|

Phenothiazine–rhodamine‐based colorimetric and fluorogenic ‘turn‐on' sensor for Zn2+ and bioimaging studies in live cells

Abstract: A phenothiazine-rhodamine (PTRH) fluorescent dyad was synthesized and its ability to selectively sense Zn 2+ ions in solution and in in vitro cell lines was tested using various techniques. When compared with other competing metal ions, the PTRH probe showed the high selectivity for Zn 2+ ions that was supported by electronic and emission spectral analyses. The emission band at 528 nm for the PTRH probe indicated the ring closed form of PTRH, as for Zn 2+ ion binding to PTRH, the λ em get shift to 608 nm was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Karmegam et al reported the phenothiazine–rhodamine based sensor 126 (Chart 5) for Zn 2+ detection. 162 In the presence of Zn 2+ ions, the absorption spectrum of 126 indicated the emergence of a new peak in a higher wavelength region (Fig. 19(a)).…”
Section: Phenothiazinementioning
confidence: 99%
“…Karmegam et al reported the phenothiazine–rhodamine based sensor 126 (Chart 5) for Zn 2+ detection. 162 In the presence of Zn 2+ ions, the absorption spectrum of 126 indicated the emergence of a new peak in a higher wavelength region (Fig. 19(a)).…”
Section: Phenothiazinementioning
confidence: 99%
“…A new rhodamine B hydrazone derivative was synthesized and showed selective response to Fe 3+ and Cu 2+ ions at 552 and 545 nm, respectively, showing the LOD of 4.63 nM (Fe 3+ ) and 526.4 nM (Cu 2+ ) (Wang et al, 2017 ). A phenothiazine-rhodamine-based fluorogenic sensor was developed for Zn 2+ with a LOD of 289 μM and demonstrated the feasibility of bioimaging use in HeLa cells (Karmegam and Subramanian, 2020 ).…”
Section: Fluorescent Molecules For Heavy Metal Ions Detectionmentioning
confidence: 99%
“…Many groups of workers have successfully developed organic chemosensors for selective detection of Zn(II) or Mg(II) via turn-on fluorescence. [36][37][38][39] We developed and characterized a mononuclear Schiff base Cd(II) complex, Cd[LH 2 I 2 ] (complex 1). As a chemosensor, this metalloligand can selectively detect Zn(II) and Mg(II) among several competitive cations via turn-on fluorescence.…”
Section: Introductionmentioning
confidence: 99%
“…Many groups of workers have successfully developed organic chemosensors for selective detection of Zn( ii ) or Mg( ii ) via turn-on fluorescence. 36–39…”
Section: Introductionmentioning
confidence: 99%